Effectiveness of Diverse Fun Learning Activities in Enhancing Foundational Numeracy Skills Among Preschool Children with Hearing Impairment - Jan, Shaik Gulab; Yadav, Santosh; Venkatesh, Prithi (JOURNAL OF INDIAN EDUCATION, 2026)
Education is vital for the all-round development of children. It will help them succeed in their life by providing knowledge and skills. Conventional learning methods provide a foundational understanding of mathematical concepts for children with hearing impairments. Still, they often lack multisensory engagement and may not fully address the unique learning needs of these children (Bradley et al. (2008). However, incorporating diverse, engaging, and fun learning activities into mathematical concepts can actively engage children, making learning enjoyable and accessible, which is especially beneficial for children with hearing impairments. So, it is essential to investigate the effectiveness of diverse, fun learning activities in improving the understanding of mathematical concepts among preschool children with hearing impairments. In this study, the term “hearing-impaired” refers to children with hearing loss, specifically with mild to moderate hearing loss, based on the ASHA classification (Clark, 1981). With this background, we have done an experimental research study on 12 control and 12 experimental groups of preschool children, employing both pre-test and post-test assessments to evaluate comprehension levels of mathematics at the preschool level. In the present study, two hypotheses were tested using paired t-tests. The pre-test comparison (Ho1) found no significant difference between the two learning methods, retaining the null hypothesis. The post-test comparison (Ho2) revealed a significant difference, with diverse, fun learning activities proving more effective than conventional methods, thus rejecting the null hypothesis. Our research study highlights the benefits of incorporating diverse, fun learning activities in educational programmes for preschool children with hearing impairment. These activities can improve the comprehension of mathematical concepts, suggesting that educators and curriculum developers integrate engaging and interactive methods into their teaching strategies to improve the learning outcomes of children with hearing impairment. This study also examines instructional strategies tailored to the sensory and communication needs of children with hearing impairment, addressing common learning constraints such as limited auditory access and language delays.